Evaporation‐Induced Self‐Assembly of Small Peptide‐Conjugated Silica Nanoparticles. Issue 42 (14th September 2021) - von Baeckmann, Cornelia; Rubio, Guilherme M. D. M.; Kählig, Hanspeter; Kurzbach, Dennis; Reithofer, Michael R.; Kleitz, Freddy
Abstract: Self‐assembly processes guide disordered molecules or particles into long‐range organized structures due to specific supramolecular interactions among the building entities. Herein, we report a unique evaporation‐induced self‐assembly (EISA) strategy for four different silica nanoparticle systems obtained through peptide functionalization of the particle surface. First, covalent peptide‐silica coupling was investigated in detail, starting with the grafting of a single amino acid (L‐serine) and expanded to specific small peptides (up to four amino acids) and transferred to different particle types (MCM‐48‐type MSNs, solid nanoparticles, and newly developed virus‐like nanoparticles). These materials were investigated regarding their ability to undergo EISA, which was shown to be independent of particle type and amount of peptide anchored to their surface. This EISA‐based approach provides new possibilities for the design of future advanced drug delivery systems, engineered hierarchical sorbents, and nanocatalyst assemblies. Abstract : Evaporation‐induced self‐assembly of a bioconjugate is reported. The formation of ring‐like structures was independent of different silica particle types and the amount of peptide conjugated to the material. This novel approach paves the way for further production of functional materials for separation, catalysis, and medical applications.